To the Side, to the Side: Academic Libraries and LibGuides Layout Adoption. Issue 3 (2nd October 2021) - Neuhaus, Chris; Gruber, Anne Marie; Cox, Angie; Koh, HyunSeung; Kelly, Jim; Bowling, Claire; Bunz, Gail
ABSTRACT: In 2014, Springshare introduced a new LibGuides layout option. In addition to the traditional horizontally-tabbed layout (top navigation), LibGuides designers now have the option of vertically-arrayed tabs on the upper left-hand side of the page (side navigation). Like the university hosting this study, schools have, to varying degrees, shifted their LibGuides toward side navigation and away from top navigation. To better understand the research behind this migration, researchers at the University of Northern Iowa conducted a thorough literature review on navigation menu location preferences and navigation menu efficacy within the field of librarianship and computer science. This review identified a complex and diverse set of results not often reported in the library literature. To gauge the extent of migration toward side navigation in LibGuides, this study investigated the navigation layout of the ten most visited LibGuides at 462 academic libraries throughout the United States during the summers of 2019 and 2021. While the majority of the LibGuides reviewed at research universities are now in side navigation format, the adoption rate of side navigation in LibGuides differed dramatically by the size and type of academic institution.